2008
DOI: 10.1111/j.1440-1746.2008.05396.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomised comparison of the FerX Ella antireflux stent and the ultraflex stent: Proton pump inhibitor combination for prevention of post‐stent reflux in patients with esophageal carcinoma involving the esophago‐gastric junction

Abstract: The antireflux stent had no demonstrable advantages compared to the combination of standard open stent and proton pump inhibitor medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 17 publications
0
33
2
Order By: Relevance
“…Two studies had a score of 4 points [6,7], eight studies had scores of 3 [4,8,10,12,[14][15][16]18], five studies scored 2 [3,9,11,13,17], and one study received one point [5]. The baseline characteristics of the patients in the trials included are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies had a score of 4 points [6,7], eight studies had scores of 3 [4,8,10,12,[14][15][16]18], five studies scored 2 [3,9,11,13,17], and one study received one point [5]. The baseline characteristics of the patients in the trials included are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…All randomized control trials (RCTs) concerning esophageal and gastroesophageal junction palliation were identified [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Studies using the conventional prosthetic tubes (Celestin or Mackler tube) were excluded since the method has fallen out of favor.…”
Section: Literature Searchmentioning
confidence: 99%
“…11,14 In addition, most patients with a stent placed across the GEJ are effectively treated with a standard open stent in combination with PPI therapy. 5 In the small selection of patients who experience persistent reflux symptoms despite PPI use, an implantable anti-reflux valve may be an option.…”
Section: Discussionmentioning
confidence: 99%
“…4 In the last decade, various anti-reflux stent designs have been tested in patients with distal esophageal cancer. [4][5][6][7][8][9][10][11] Clinical success with regard to relief of dysphagia and reflux symptoms, however, varies considerably between stent designs. Because some anti-reflux stents are associated with high migration rates, 4 it is not generally recommended to place anti-reflux stents in all patients with GEJ cancer.…”
mentioning
confidence: 99%
“…Although some of the stents appeared effective in reducing gastroesophageal reflux, further research is required to confirm this favorable outcome [29][30][31][32][33][34]. During the start of radiotherapy, dysphagia often increases due to mucositis and esophagitis.…”
Section: Technical Considerationsmentioning
confidence: 95%